2021
DOI: 10.1126/sciadv.abf6397
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear infrared polaritonic interaction between cavities mediated by molecular vibrations at ultrafast time scale

Abstract: Realizing nonlinear interactions between spatially separated particles can advance molecular science and technology, including remote catalysis of chemical reactions, ultrafast processing of information in infrared (IR) photonic circuitry, and advanced platforms for quantum simulations with increased complexity. Here, we achieved nonlinear interactions at ultrafast time scale between polaritons contained in spatially adjacent cavities in the mid-IR regime, altering polaritons in one cavity by pumping polariton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 32 publications
(47 reference statements)
0
47
0
Order By: Relevance
“…Strong coupling between electronic states of matter and resonant optical cavities has played a key role in the development of novel states of quasi-particles, such as Bose–Einstein condensation and lasing in exciton-polaritons. , Very recently, there has been a sharp increase in chemical applications of strong coupling, led by the discoveries of Ebbesen et al, who found that chemical reactivity can be altered by vibrational strong coupling. Infrared spectroscopy of vibrational strong coupling offers direct access to the polaritonic states, and ultrafast pump–probe or 2D spectroscopy enables determination of relaxation and dephasing in these novel hybrid light–matter states. The promise of cavity-controlled chemistry is sufficiently great that intense investigation is clearly warranted. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong coupling between electronic states of matter and resonant optical cavities has played a key role in the development of novel states of quasi-particles, such as Bose–Einstein condensation and lasing in exciton-polaritons. , Very recently, there has been a sharp increase in chemical applications of strong coupling, led by the discoveries of Ebbesen et al, who found that chemical reactivity can be altered by vibrational strong coupling. Infrared spectroscopy of vibrational strong coupling offers direct access to the polaritonic states, and ultrafast pump–probe or 2D spectroscopy enables determination of relaxation and dephasing in these novel hybrid light–matter states. The promise of cavity-controlled chemistry is sufficiently great that intense investigation is clearly warranted. …”
mentioning
confidence: 99%
“…The fundamental spectroscopy and dynamics of vibrational polaritons present new avenues in understanding and manipulating quantum dynamics using the external influence of a cavity. Several recent reports of transition metal complexes, particularly the strong triply degenerate W­(CO) 6 stretching vibrations, coupled to resonant cavities have considered the nonlinear optical response of vibrational polaritons in various conditions of weak and strong coupling. , A key proposal to explain the observed relaxation dynamics posits that the polariton states relax to the uncoupled reservoir molecules. Subsequent excited state absorption from the v = 1 to v = 2 state of these reservoir molecules is thought to account for the substantial signal amplitude at the lower polariton detection frequency due to a coincidental energy matching of the 1–2 transition and the LP frequency.…”
mentioning
confidence: 99%
“…In the field of quantum optics, light matter interaction plays an important role in optoelectronic devices 1 4 , sensing 5 , infrared (IR) nano-antennas 6 , mid-infrared molecular vibrations driven by femto-second lasers 7 as well cavity quantum electrodynamics (QED) and nano-resonnators 8 , 9 . Furthermore, it provides significant insights to the field of bio-photonic medical sciences based on the analysis of the near infrared light (NIR) of biological complexe structures 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this seminal observation 13 from the Ebbesen group, intensive experimental and theoretical efforts have now been made to understand VSCrelated chemistry. From an experimental point of view, there has been an extensive exploration of VSC catalytic effects in different types of chemical reactions [14][15][16][17][18][19][20] and the use of VSC to alter other molecular properties in the absence of an external laser pumping 21 has also been investigated; at the same time, spectroscopists have also focused on the ultrafast dynamics of vibrational polaritons by pump-probe 22,23 and two-dimensional infrared (IR) [24][25][26][27][28][29] spectroscopies. From a theoretical point of view, while the detailed mechanism of "VSC catalysis" is still not well understood [30][31][32][33][34][35][36][37][38] , the current models of ultrafast polariton dynamics appear to be largely consistent with observations [39][40][41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%